Personal Digital Archiving Practices of Library and Information Science Student at Padang State University - Putri, Inggi Eka Mei; Rahmah, Elva (Darul Yasin Al Sys, 2026)
This study aims to describe the personal digital archiving capabilities of Library and Information Science students at Universitas Negeri Padang, specifically those from the 2023 and 2024 cohorts. A descriptive quantitative approach was employed, involving 61 participants selected through proportionate stratified random sampling. Data were collected through questionnaires and supported by documentation, while the research instruments and data were examined using expert judgment, validity and reliability testing, and descriptive statistical analysis. The findings indicate that students’ personal digital archiving practices are in the high category, with a grand mean score of 3.18. This result suggests that students demonstrate competent abilities in managing personal digital archives across different stages, although their implementation is not yet fully optimal or consistent. The study contributes to the growing literature on digital information management by providing empirical insight into students’ personal digital archiving capabilities. Practically, the findings highlight the need for educational institutions to develop more structured and sustainable digital archiving practices. Future research is recommended to examine additional variables and broader contexts to generate more comprehensive findings.